Additive Manufacturing and Supply chains in the Consumer Goods Industry: A Systematic Review - Sanusi, Mubaraq (2021)
As supply chains in various industries ranging from aerospace to consumer goods are starting to embrace Additive Manufacturing technology to gain competitive advantage and other remarkable benefits, the research community is looking to evaluate the implications of this and what the future holds. This article focuses on the consumer goods industry and aims to add to the ongoing scientific discourse by systematically reviewing relevant literature in the space, both academic and grey literature. The review encompasses 113 articles, where 35 were subjected to a full-text analysis with content-based coding using an inductive approach. Findings revealed the key Additive Manufacturing domains trends for consumer goods supply chains as well as the existing and likely implications for the future for each identified domain. In addition, based on a qualitative analysis, future research avenues were identified.